Body Image Among Junior High School Students in a Coastal Tourism Area - pika nurafipah (Jendela Nursing Journal (JNJ), 2026)
Background: body image is a key aspect of adolescents’ self-concept that can influence their psychological well-being and social behavior. Adolescence is marked by various physical, psychological, and social changes. Body image issues generally arise alongside these changes and, in some cases, can become obstacles, such as decreased self-confidence and self-dissatisfaction. The phenomenon of negative body image among adolescents is a significant concern, particularly among adolescents living in coastal tourism areas with unique social and cultural characteristics. Purpose: this study aims to examine the body image of students at Pangandaran State Junior High School 1 who live in a coastal tourism area. Methods: this study is a quantitative descriptive study with a population of 1,023 individuals. The sample consisted of 288 participants, selected using proportionate stratified random sampling. The instrument used was the Multidimensional Body-Self Relations Questionnaire-Appearance Scale (MBSRQ-AS), and data analysis employed univariate techniques, with results presented as percentages. Results: the results showed that 163 respondents (56.6%) fell into the positive category and 125 respondents (43.4%) fell into the negative category. When viewed by dimension, respondents had positive perceptions in the dimensions of appearance evaluation (53.1%), body area satisfaction (55.2%), and self-classified weight (61.8%), and negative perceptions in the dimensions of appearance orientation (50.3%) and overweight preoccupation (53.1%). Conclusion: Positive body image among the majority of respondents has not been accompanied by good self-care behaviors; therefore, it is recommended that institutions enhance health promotion education and interventions and foster a supportive social environment, given that environmental factors play a significant role in shaping adolescents’ body perceptions. Keywords: Adolescence; Body Image; Body Perception; Coastal Areas